BYOD 환경을 고려한 모바일 웹을 위한 세션 관리 개선 방안 연구 - 김영훈; 박용석; Kim, Young-hun; Park, Yongsuk (한국정보통신학회논문지, 2015)
This paper explains a web session management system for mobile web environment with BYOD(Bring Your Own Device). This system operates by enhanced secure session token. This system consists of an unique identifier, time stamp, and encryption algorithm. The Unique identifier in this system classifies each mobile device for web security based on mobile environment with BYOD. And the Time stamp in this system that determine session effectiveness for web security. Also the Cipher algorithm in this system that protects session token information for web security. This paper analysis a security of session management system running on mobile web environment using the simulation techniques. The proposed method is more suitable than the other methods under enviroment mobile web environment with BYOD. 본 논문은 BYOD(Bring Your Own Device)를 포함한 모바일 웹 환경을 위한 웹 세션 관리 시스템에 대해서 기술한다. 이 시스템은 보안이 강화된 세션 토큰으로 운영되며, 고유 식별자, time stamp, 암호 알고리즘으로 구성된다. 시스템에서 고유 식발자는 BYOD를 포함한 모바일 환경에서 보안을 위하여 각 단말기를 구분한다. 시스템에서 time stamp는 BYOD를 포함한 모바일 환경에서 보안을 위하여 세션 유효성을 판단한다. 시스템에서 암호 알고리즘은 세션 토큰의 내부 정보를 보호한다. 본 논문은 시뮬레이션 기법을 사용해서 모바일 웹 상에서 세션 관리 시스템의 보안성을 분석한다. 제시된 방법은 기존 방법에 비하여 BYOD 환경의 모바일 웹 보안에 있어서 더 적합하다.